2016
DOI: 10.1016/j.jfca.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and protein quality of common pheasant (Phasianus colchicus) reared in semi-extensive conditions

Abstract: Common pheasant (Phasianus colchicus) is a species with potential to produce high quality meat. Rearing these birds in semi-extensive regime for other purposes than just for hunting has drawn producers' attention. This study aimed to evaluate the lipid and protein composition of breast and leg meat from male and female pheasant. Meat portions exhibited significant differences between total lipid (1.3 and 3.5 g/100g), total cholesterol contents (0.5 and 0.57mg/g), fatty acids profile, protein content (89 and 82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 25 publications
7
20
1
Order By: Relevance
“…On the other hand, Łukasiewicz et al (2011) found that the breast muscles of female pheasants had higher concentrations of monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs), including n-3 and n-6 PUFAs, and a lower n-6/n-3 PUFA ratio. According to Quaresma et al (2016), an analysis of the fatty acid profile of pheasant meat should account for the age of birds because in the order Galliformes, females begin to deposit lipids at a younger age than males. As a result, young males and females differ with regard to both the amount and composition of deposited body fat.…”
Section: Fatty Acid Profilementioning
confidence: 99%
“…On the other hand, Łukasiewicz et al (2011) found that the breast muscles of female pheasants had higher concentrations of monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs), including n-3 and n-6 PUFAs, and a lower n-6/n-3 PUFA ratio. According to Quaresma et al (2016), an analysis of the fatty acid profile of pheasant meat should account for the age of birds because in the order Galliformes, females begin to deposit lipids at a younger age than males. As a result, young males and females differ with regard to both the amount and composition of deposited body fat.…”
Section: Fatty Acid Profilementioning
confidence: 99%
“…Common pheasant meat is a rich source of proteins and microelements and contains small amounts of lipids with a low content of saturated fatty acids and cholesterol. These aspects attract consumers that pay more attention to healthy life style (Kotowicz, Lachowicz, Lisiecki, Szczygielski, & Zych, ; Quaresma et al, ). Indeed, common pheasant meat as well as chicken ( Gallus gallus L.), turkey ( Meleagris gallopavo L.), common quail ( Coturnix coturnix L.), and ostrich ( Struthio camelus L.) meats are an attractive alternative to red meat (Hoffman & Wiklund, ), also including some bird species less accessible to Europeans, such as emu ( Dromaius novaehollandiae Latham), Japanese quail ( Coturnix japonica L.), and bobwhite ( Colinus virginianus L.).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic peroxides, biclyclic endoperoxides, and hydroperoxyl are some of its major precursors (Lima et al, 2013;Amaral et al, 2018). MDA is important for industry and scientific research since it can be used to determine lipid peroxidation through the TBARS test (Thiobarbituric Acid Reactive Substances), the most widely used assay to assess the effects of lipid oxidation on meat and meat products (Min and Ahn, 2005;Amaral et al, 2018). Another important secondary oxidation products are the volatile compounds responsible for the off-odor and off-flavor such as propanal, hexanal and pentanal (Barriuso et al, 2013;Lorenzo et al, 2013;Guyon et al, 2016;Cunha et al, 2018).…”
Section: Article Infomentioning
confidence: 99%
“…Meat from wild-living game is a highly valued food El-Ghareeb et al, 2009;Hofbauer et al, 2010). Currently, the common pheasant is the most abundant, widespread and economically important non-migratory game bird in Europe (CABS, 2010;Quaresma et al, 2016). In the past, animals were mostly associated with hunting, but nowadays, a freely available commodity is increasing in popularity (Standarová et al, 2012;Hrabčáková et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation